Vogt-Koyanagi-Harada Syndrome Following COVID-19 mRNA Vaccination: Th2 to Th1 Transition-related Molecular Machinery - Yasuaki Ikuno; Akihiko Yamaguchi; Toshifumi Takahashi; Noriki Fujimoto (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)